IMPLEMENTASI APLIKASI TUR VIRTUAL 360 BERBASIS VIRTUAL REALITY UNTUK PENGENALAN KAMPUS UNITAMA - Muhajirin; Rahman Nasir, Khaidir; Annah; Nugroho, Muhammad Syarif (PROGRESS, 2025)
This research focuses on the development of an Android-based virtual tour application to introduce the facilities and infrastructure of Universitas Teknologi Akba Makassar (UNITAMA) using Virtual Reality (VR) technology and the 360-degree panoramic image method. The objective of this study is to create an interactive medium for students, prospective new students, and their parents to access detailed information about the campus environment. The research employs the Multimedia Development Life Cycle (MDLC) method, consisting of concept, design, material collection, assembly, testing, and distribution. Testing results using the Blackbox method showed that the application functions properly, while user experience evaluation recorded an average score above 91%, with clarity achieving the highest score of 98.3%. This indicates that the application is effective as a digital campus introduction medium and provides an interactive and realistic experience..